2020
DOI: 10.1111/are.14745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term starvation periods on flesh quality in Arctic charr (Salvelinus alpinus)in different seasons

Abstract: Possible effects of short‐term starvation on flesh quality in Arctic charr were studied in spring (March) and summer (August). Groups of juvenile Arctic charr (mean weight March 536 g ± 24; August 461 g ± 15 SEM) were starved for 1, 2 and 4 weeks (March) and 1, 2 and 3 (August). After each starvation period, the fish were slaughtered, and flesh samples collected in order to investigate quality and textural properties in the different experimental groups. Starvation had a positive effect on flesh quality giving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…Previous studies on the effects of environmental factors, such as temperature, on aquaculture fish have mainly focused on their effect on fish growth (Imsland, et al., 2020). However, sensory quality is also very important for the marketability of the product (Carlberg et al., 2018; Imsland et al., 2020) and the results of the present study show that temperature rearing regime affects the flesh quality in Arctic charr. Lower temperatures appear to promote better quality.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies on the effects of environmental factors, such as temperature, on aquaculture fish have mainly focused on their effect on fish growth (Imsland, et al., 2020). However, sensory quality is also very important for the marketability of the product (Carlberg et al., 2018; Imsland et al., 2020) and the results of the present study show that temperature rearing regime affects the flesh quality in Arctic charr. Lower temperatures appear to promote better quality.…”
Section: Discussionsupporting
confidence: 52%
“… 218 Similar results were observed in sea bass, which showed higher flesh firmness and collagen contents after fasting for 12 days 222 . In Arctic charr ( Salvelinus alpinus ), 3 weeks of starvation led to harder texture and less gaping in the fillet 219 . Further analyses revealed that the starved fish showed lower muscle cathepsin activity than those fed continuously, indicating the delay of collagen degradation.…”
Section: Strategies To Regulate Texture Characteristics In Aquaculturesupporting
confidence: 64%
“…With improvements in people's living standards, consumers have begun to exhibit a greater desire for high-quality fish ( Liu et al., 2020 ). The flesh quality of muscle, which is the main edible part of the fish, is not only affected by the internal factors of the fish, such as strain ( Johnston et al., 2006 ) and size ( Shearer, 1994 ), but also by external factors, such as feed ( Sun et al., 2018 ; Zhao et al., 2019 ), feeding strategy ( Lv et al., 2018 ; Imsland et al., 2020 ), temperature ( López-Albors et al., 2008 ), density ( Álvarez et al., 2020 ; Birolo et al., 2020 ; Silva et al., 2020 ), salinity ( Cheng et al., 2020 ), dissolved oxygen ( Zuanazzi et al., 2019 ), and other environmental factors. The levels of nutrients, such as mineral elements ( Zhang et al., 2016a ), fatty acids ( Li, 2020a ), amino acids ( Cai et al., 2018 ), and proteins ( Zhang et al., 2016b ) in feed, along with the source of protein ( Wang et al., 2017 ), play an important role in regulating flesh quality.…”
Section: Introductionmentioning
confidence: 99%